Characterizing components of and attendance at resident‐driven Housing First programming in the context of community‐based participatory research. Issue 5 (10th December 2020) - Collins, Susan E.; Goldstein, Silvi C.; King, Victorio L.; Orfaly, Victoria E.; Gu, Jingyan; Clark, Alex; Vess, Alexander; Lee, Gary; Taylor, Emily M.; Fentress, Taurmini; Braid, Ashley K.; Clifasefi, Seema L.
Abstract: Aims: This secondary study characterized components of and engagement in the life‐enhancing alcohol‐management program (LEAP), which is resident‐driven housing first programming. Methods: We used a process akin to conventional content analysis to operationalize the LEAP according to its component activities. We used generalized linear modeling to identify predictors of LEAP activity participation and to predict alcohol and quality‐of‐life outcomes from participation in specific LEAP activities categories. Results: Overall, 86% of participants attended at least one LEAP activity, which comprised three categories: administrative leadership opportunities, meaningful activities, and pathways to recovery. Employment status alone predicted LEAP activity attendance: Employed residents attended 88% fewer LEAP activities than unemployed residents. Participants who sought out more pathways to recovery activities were more likely daily drinkers and more impacted by alcohol‐related harm. Those engaging in administrative leadership opportunities were overall less impacted by alcohol use and had a higher quality of life generally, and their alcohol outcomes further improved over time. Conclusions: Programming developed with Housing First residents was well‐attended but could be made more inclusive by including evening programming to accommodate residents employed full time and engaging more severely impacted participants in administrative leadership activities, where the greatest benefits of programming were seen.